Plant ascorbate peroxidase: molecular phylogeny and role in oxidative stress - Imola FÁBIÁN; Edina TÖRÖK; Dorina PODAR; Gyöngyi SZÉKELY (Studia Universitatis Babeș-Bolyai. Biologia)
Oxidative stress appears as a condition in accumulation and detoxification of reactive oxygen species (ROS). ROS are oxygen-derived free radicals, generated predominantly in mitochondria, peroxisomes and chloroplasts, as natural byproducts of the normal cell aerobic metabolism. In spite of their damaging effect, ROS can act as secondary messengers in different cellular processes, including tolerance to environmental stress factors. To neutralize the harmful effects of ROS, plants have evolved enzymatic and non-enzymatic defense systems. In flowering plants, ascorbate peroxidase (APX) is present in eight isoenzyme forms and constitutes an important enzymatic component in scavenging the harmful hydrogen peroxide to water as part of ascorbate-glutathione cycle. APX proteins, their roles, in planta expression location and their phylogenetic relationships are presented in the current paper. The phylogenetic analysis performed with the maximum likelihood method which was established for 118 protein sequences of 45 flowering plants. Our phylogenetic analysis revealed diversification of ascorbate peroxidase in angiosperms, and indicates a close relationship of APX1 with APX2, APX3 with APX4 and APX5, and APX6 with sAPX and tAPX proteins. Evolutionary relationships of plant ascorbate peroxidase isoenzymes indicate the evolution of different plant species genome and their phylogenetic affiliation.